Diverse prognostic value of the GTn promoter polymorphism in squamous cell and adeno carcinoma of the oesophagus. Issue 4 (6th May 2016) - Ghadban, T.; Miro, J.T.; Trump, F.; Tsui, T.Y.; Uzunoglu, F.G.; Reeh, M.; Gebauer, F.; Bachmann, K.; Wellner, U.; Kalinin, V.; Pantel, K.; Izbicki, J.R.; et al.
Abstract : Abstract : The basal transcription of heme oxygenase‐1 (HO‐1) regulation is dependent upon a GT repeat germ line polymorphism (GTn) in the promoter of the HO‐1 gene. We determined the prognostic value of HO‐1 promoter polymorphism on the natural postoperative course of complete resected oesophageal cancer. Genomic DNA from 297 patients was amplified by polymerase chain reaction and sequenced. The results were correlated with clinicopathological parameters, disseminated tumour cells in bone marrow (DTC) and clinical outcome. Depending on short allele with <25 and long allele with ≥25, GTn repeats three genotypes (SS, SL and LL) were defined. A diverse role of GTn was evident in squamous cell carcinoma (SCC) and adenocarcinoma (AC). In SCC, the SS genotype presented less advanced tumours with lower rate DTC in bone marrow and relapse compared with L‐allele carriers. In contrast, AC patients with the SS genotype displayed a complete opposing tumour characteristic. The disease‐free (DFS) and overall survival (OS) in SCC patients was markedly reduced in LL genotypes (p < 0.001). In AC contrarily the SS genotype patients displayed the worst DFS and OS (p < 0.001). GTn is a strong prognostic factor with diverse prognostic value for recurrence and survival in AC and SCC.